2009
DOI: 10.3767/003158509x461701
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and taxonomy of obscure genera of microfungi

Abstract: The recently generated molecular phylogeny for the kingdom Fungi, on which a new classification scheme is based, still suffers from an under representation of numerous apparently asexual genera of microfungi. In an attempt to populate the Fungal Tree of Life, fresh samples of 10 obscure genera of hyphomycetes were collected. These fungi were subsequently established in culture, and subjected to DNA sequence analysis of the ITS and LSU nrRNA genes to resolve species and generic questions related to these obscur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
103
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(108 citation statements)
references
References 36 publications
5
103
0
Order By: Relevance
“…This fungus, sometimes considered rare (Crous et al 2009), is world-wide and not rare in Washington State. It is a minor pathogen of several plants, and once was recorded as the dominant fungus (contaminant) on Washington wheat grain (Goetz and Dugan 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This fungus, sometimes considered rare (Crous et al 2009), is world-wide and not rare in Washington State. It is a minor pathogen of several plants, and once was recorded as the dominant fungus (contaminant) on Washington wheat grain (Goetz and Dugan 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Seifert et al (2007) treated Seifertia in Dothideomycetes based on the large subunit LSU gene sequence data and it clustered with Mycosphaerella mycopappi, but was unrelated to Mycosphaerella sensu stricto. Crous et al (2009) re-examined Xenostigmina and confirmed that Xenostigmina is a synanamorph of Mycopappus and showed to be allied with Seifertia in Pleosporales. Furthermore, Crous et al (2013) revealed that Xenostigmina and Mycopappus clustered in the Phaeosphaeriaceae.…”
Section: Discussionmentioning
confidence: 99%
“…Based on phylogenetic analysis of LSU sequence data, Seifert et al (2007) treated Seifertia azalea in Dothideomycetes, as closely related to Mycosphaerella mycopappi A. Funk & Dorworth, but unrelated to Mycosphaerella sensu stricto. Crous et al (2009Crous et al ( , 2013 placed Seifertia in Pleosporales which was shown to be allied to Xenostigmina, a synanamorph of Mycopappus, based on combined ITS and LSU phylogenetic analyses. There is little molecular data to resolve the natural placement of Seifertia in Dothideomycetes.…”
Section: Introductionmentioning
confidence: 99%
“…The 5.8S nuclear ribosomal gene with the two flanking internal transcribed spacers (ITS) and 28S nrDNA sequence (LSU) genes were amplified and sequenced using the primer pairs ITS-1F + ITS-4R (White et al 1990) and LR5 + LROR (Crous et al 2009), respectively. The sequence quality was checked using Sequence Scanner Software v1 (Applied Biosystems).…”
Section: Dna Isolation and Pcr Analysismentioning
confidence: 99%
“…Asexual fungi may lack or have unknown sexual stages, and were previously difficult to classify in a natural system. However, with molecular sequence data it is now possible to resolve their taxonomic hierarchy and phylogenetic affinity (Crous et al 2009). In this paper, we report on the phylogenetic affinities of three asexually reproducing fungi, Bahusandhika indica (Subram.)…”
Section: Introductionmentioning
confidence: 99%